Integrasi Konseling Multibudaya dalam Eksplorasi Nilai Kearifan Lokal Budaya “Pappaseng” pada Suku Bugis - Buana, Imanda Riski Tri; Rakhmanita, Aulia; Jannah, Ilda Miftakhul; Rachmawati, Amalia Putri; Nabella, Kharisma Putri; Khusumadewi, Ari (TSAQOFAH, 2025)
Integrating local values into multicultural counseling represents a strategic step toward enhancing cultural sensitivity and contextual relevance in counseling practices in Indonesia. This study aims to analyze and integrate the cultural value of pappaseng, a foundational principle of communication and character in Bugis culture into a multicultural counseling approach. The method used is a Systematic Literature Review (SLR), encompassing stages of identification, selection, evaluation, and synthesis of 17 scholarly articles discussing multicultural counseling, local wisdom, and Bugis cultural values. The analysis reveals that pappaseng holds significant potential in reinforcing ethical, empathetic, and culturally oriented communication between counselors and clients. These values support the development of more inclusive counseling relationships based on an understanding of clients’ cultural backgrounds, thereby enhancing the overall effectiveness of the counseling process. The findings contribute theoretically to the development of multicultural counseling approaches grounded in local wisdom and offer practical implications for counselors seeking to apply cultural values as a foundation for more contextual and meaningful interventions.